Causes of variations of trace and rare earth elements concentration in lakes bottom sediments in the Bory Tucholskie National Park, Poland - Mariusz Sojka (Nature Portfolio, 2021)
Abstract The objective of this study was to analyse spatial variability of the trace elements (TEs) and rare earth elements (REEs) concentration in lake bottom sediments in Bory Tucholskie National Park (BTNP); Poland. The following research questions were posed: which factors have a fundamental impact on the concentration and spatial variability of elements in bottom sediments, which of the elements can be considered as indicators of natural processes and which are related to anthropogenic sources. The research material was sediments samples collected from 19 lakes. The concentrations of 24 TEs and 14 REEs were determined. The analyses were carried out using the inductively coupled plasma mass spectrometry (ICP-QQQ). Cluster analysis and principal component analysis were used to determine the spatial variability of the TEs and REEs concentrations, indicate the elements that are the indicators of natural processes and identify potential anthropogenic sources of pollution. The geochemical background value (GBV) calculations were made using 13 different statistical methods. However, the contamination of bottom sediments was evaluated by means of the index of geo-accumulation, the enrichment factor, the pollution load index, and the metal pollution index. The BTNP area is unique because of its isolation from the inflow of pollutants from anthropogenic sources and a very stable land use structure over the last 200 years. This study shows high variability of TE and REE concentrations in lake sediments. The values of geochemical indices suggest low pollution of lakes bottom sediments. It was found that TEs originated mainly from geogenic sources. However, the concentrations of Li, Ni, Sc, Se, Be, Se, Ag, Re, Tl, Cd, Sb and U may be related to the impact of point sources found mainly in the Ostrowite Lake. Almost all REEs concentrations were strongly correlated and their presence was linked to with geochemical processes. The elements allowing to identify natural processes and anthropogenic pollution sources were Cr, Co, Cu, Ag, Cd, Zn, Bi, Re, Ba, Al and Rb in TEs group and Nd, Gd, Yb, Lu, Eu, Dy and Ce in REEs group. The analysis shows high spatial variability of TE and REE concentrations in lake sediments. The values of geochemical indices point to low pollution of lakes sediments. The anthropogenic sources only for two lakes had an impact on concentrations of selected TEs and REEs. The analyses allowed to identify elements among TEs and REEs documenting geochemical processes and those indicating anthropogenic sources of pollution.